Throw Them All in One Pot? Differences in Stereotypes About Subgroups of Pre-Service Teachers - Stuckert, Martin O.; Ihme, Toni A.; Südkamp, Anna; Möller, Jens (Frontiers in Education, 2021)
According to the stereotype content model, stereotypes can be described by using the dimensions competence and warmth. Compared to other professions, teaching is associated with a paternalistic stereotype consisting of high warmth and low competence. In four studies, stereotypes about different subgroups of pre-service teachers were compared. The aim was to understand sub-stereotypes better that could lead to different levels of stereotype threat and adverse behavioral tendencies. In Study 1 (N = 335), we compared stereotypes about elementary school pre-service teachers, grammar school pre-service teachers, computer science students, law students, and psychology students reported by pre-service teachers and psychology students. In contrast to nonteaching students, both groups of pre-service teachers corresponded to the paternalistic stereotype. In Study 2 (N = 243), pre-service teachers reported stereotypes about pre-service teachers for elementary schools, special education schools, comprehensive schools, vocational schools, and grammar schools. Elementary school pre-service teachers were stereotyped most paternalistically, while grammar school pre-service teachers matched the paternalistic stereotype the least. The ratings of other school types mostly fell between these extremes. In Studies 3a (N = 133, open-ended questions) and 3b (N = 308, closed-ended questions), students of various study programs compared pre-service teachers majoring in German and history (representing a non-STEM major combination) to pre-service teachers with the majors mathematics and physics (representing a STEM major combination). Pre-service teachers studying German and history were rated warmer but less competent than pre-service teachers with the majors mathematics and physics, confirmed by both methods of measuring stereotypes. In Studies 1, 3a, and 3b, ingroup favoritism in the ratings by pre-service teacher participants was tested and only found for competence in Study 1. The importance of our results and their implications for stereotype threat effects and possible interventions are discussed.